Circular RNA circNRIP1 Sponges microRNA-138-5p to Maintain Hypoxia-Induced Resistance to 5-Fluorouracil Through HIF-1α-Dependent Glucose Metabolism in Gastric Carcinoma - Xu G; Li M; Wu J; Qin C; Tao Y; He H (Cancer Management and Research, 2020)
Guangsong Xu, Mingliang Li, Jiang Wu, Chunhong Qin, Yin Tao, Hongjie He Department of General Surgery, The Second Affiliated Hospital of University of South China, Hengyang 421001, Hunan Province, People’s Republic of ChinaCorrespondence: Hongjie HeDepartment of General Surgery, The Second Affiliated Hospital of University of South China, 35 Jiefang Avenue, Hengyang 421001, Hunan Province, People’s Republic of ChinaEmail hehj_surgery@163.comBackground: Hypoxia-induced chemoresistance is recognized as a major obstacle to the successful treatment of gastric cancer (GC). Circular RNAs (circRNAs) have been proposed to implicate in resistance to chemotherapeutic drugs. However, whether circNRIP1 is involved in the development of hypoxia-induced 5-fluorouracil (5-FU) resistance remains largely unknown.Methods: Gene expression was evaluated using quantitative real-time polymerase chain reaction and Western blot. The impact of circNRIP1 on hypoxia-induced resistance to 5-FU was investigated by determining glucose consumption, lactate production and glucose-6-phosphate (G6P) levels. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolim bromide assay was performed to assess cell survival.Results: circNRIP1 was upregulated in GC cells. Hypoxia induced the upregulation of circNRIP1 and reduced the sensitivity of GC cells to 5-FU, as evidenced by the increase in multidrug resistance 1 gene, P-glycoprotein, hypoxia-inducible factor-1α (HIF-1α) and G6P levels, glucose consumption, lactate production, as well as cell survival. Silencing of circNRIP1 enhanced the sensitivity of GC cells to 5-FU under a hypoxic condition. microRNA (miR)-138-5p was confirmed as a downstream target gene of circNRIP1, and upregulation of miR-138-5p could reverse the effect of circNRIP1 on hypoxia-induced 5-FU resistance. Additionally, HIF-1α was a target gene of miR-138-5p. More significantly, the effect of circNRIP1 on hypoxia-induced 5-FU resistance was markedly blocked by 2-DG treatment.Conclusion: circNRIP1 functioned as a miR-138-5p sponge to enhance hypoxia-induced resistance to 5-FU through modulation of HIF-1α-dependent glycolysis, which provides a novel potential approach to overcome hypoxia-induced 5-FU resistance in GC.Keywords: 5-fluorouracil, gastric carcinoma, circular RNA circNRIP1, miR-138-5p, multidrug resistance 1 gene, P-glycoprotein, hypoxia-inducible factor-1α, glucose-6-phosphate